Role of Oceanic Internal Instability in the Generation of Low‐Frequency Variability in the Indian Ocean - S. Anjana; A. Chatterjee; W. Han; S. Prerna; C. K. Sajidh (Geophysical Research Letters, 2023)
Abstract Low‐frequency (Interannual and longer timescale) variability in sea surface temperature (SST) of the Indian Ocean plays a crucial role in affecting the regional climate. Using a high‐resolution global model simulation, we show that internal oceanic variability is an important cause of the observed low‐frequency variability in the subtropical‐midlatitude south Indian Ocean (SIO) between 20° and 40°S, a marked southward shift in the latitude band of active internal variability for the low‐frequency compared to earlier estimates based on coarser Indian Ocean regional models. Notably, we show that internal variability does not contribute to the observed low‐frequency variability in the Seychelles−Chagos thermocline ridge region. Energy budget analysis shows that baroclinic instability is the primary cause for the internal variability. The slowly growing baroclinic instabilities at low frequency and longer length scale favor Rossby waves' generation, propagating the SST and sea level anomaly signals westward.